2021
DOI: 10.1080/07908318.2021.1898630
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the ‘ideal native speaker’ teacher in early childhood education

Abstract: Current foreign language education policies advocate plurilingual approaches to learning and teaching languages and call into question the 'ideal native speaker' as the ultimate model. Observations within a teacher training context indicate that this ideal still holds considerable weight among pre-service teachers. A study was carried out with students enrolled on the degree programme in Early Childhood Education at a university in Catalonia to explore the extent to which the 'ideal native speaker' model preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…By labeling teachers as separate "native speakers" and "non-native speakers, " it falsely positions them as culturally superior and inferior with separate roles and attributes" (Holliday, 2018: 1). Waddington (2021) provides evidence that the "ideal native speaker" model prevails in pre-service teacher assumptions and beliefs and that the latter not only serve to perpetuate the ideal itself, but also reinforce disempowering and discriminatory attitudes among the profession, which are both outdated and incongruent with current multilingualism inspired policies in early childhood education.…”
Section: Contrasting Viewsmentioning
confidence: 95%
“…By labeling teachers as separate "native speakers" and "non-native speakers, " it falsely positions them as culturally superior and inferior with separate roles and attributes" (Holliday, 2018: 1). Waddington (2021) provides evidence that the "ideal native speaker" model prevails in pre-service teacher assumptions and beliefs and that the latter not only serve to perpetuate the ideal itself, but also reinforce disempowering and discriminatory attitudes among the profession, which are both outdated and incongruent with current multilingualism inspired policies in early childhood education.…”
Section: Contrasting Viewsmentioning
confidence: 95%
“…They developed new beliefs about teaching preschool children and their beliefs became more concrete and concerned age-specific criteria related to designing activities and materials and assessments. Waddington (2021) analyzed the impact of a FL teacher training program embedded as an innovation in the early childhood degree program at a Spanish university. Based on analysis of data collected by questionnaires and focus group discussions administered before and after the course, she found that participants' initial preferences for FL native speakers and FL specialists as ideal FL teachers to preschoolers changed by the end of the program.…”
Section: Studies On Teachersmentioning
confidence: 99%
“…In order to effectively instruct young learners, one must have a comprehensive understanding of how young learners development influences linguistic acquisition (Nguyen, 2019;Vieira et al, 2022). There is a wide range of linguistic competence, cognitive ability, and learning style among the young students in TEYL courses (Waddington, 2022). It might be difficult for aspiring pre-service teachers to successfully differentiate education to fit the requirements of the learners.…”
Section: Pre-service Teachers' Challenges In Teylmentioning
confidence: 99%